In-plane soil-structure interaction in layered, fluid-saturated, poroelastic half-space II: Pore pressure and volumetric strain. Issue 92 (January 2017) - Liang, Jianwen; Fu, Jia; Todorovska, Maria I.; Trifunac, Mihailo D.
Abstract: Parts I and II of this paper present a study of linear in-plane soil-structure interaction in fluid-saturated, poroelastic, layered half-space using the Indirect Boundary Element Method (IBEM). The structure is a shear wall supported by a rigid embedded foundation. Part I presented the methodology and results for the foundation and structure responses. Part II (this paper) presents a parametric study in the frequency domain of the pore pressure, and of the volumetric strain in the solid frame and the pore fluid (water in this case) along the soil-foundation interface and the ground surface. The presented results are for the special case of a single soil layer over bedrock, semi-circular foundation and zero seepage force. The analysis of peaks in the pore pressure response versus dimensionless frequency suggests that they occur near the system frequencies and near the soil layer resonant frequencies, to a degree that depends on the incident wave. For example, for vertically incident SV wave, they occur mostly near the system frequencies, while, for incident P wave, they occur also near the soil layer resonant frequencies. The results of this linear model may be useful for better understanding of how the soil-structure interaction contributes to pore pressure buildup near foundations of structures, which may eventually lead to soil liquefaction and severe consequences in the stability of the structure. Highlights: Dynamic soil-structure interaction in layered poroelastic half-space. Biot's theory for waves in fully saturated poroelastic medium and Indirect Boundary Element Method. Two-dimensional structure on rigid foundation with coupled horizontal and rocking response. Excitation by plane P and SV waves. Peaks in pore pressure depend on system frequency and soil layer resonant frequency.